2001
DOI: 10.1248/bpb.24.425
|View full text |Cite
|
Sign up to set email alerts
|

Possible Changes in Expression of Chemotaxin LECT2 mRNA in Mouse Liver after Concanavalin A-Induced Hepatic Injury.

Abstract: /nu؊ ) mice, the increase in TNF-a a and IFN-g g mRNA expression was found to be closely related to a reduction in LECT2 mRNA expression. These results suggest that the reduction in expression of LECT2 mRNA is not directly involved in apoptosis and may be inversely related to the expression of TNF-a a and/or IFN-g g mRNA in the injured liver.Key words leukocyte-derived chemotaxin 2; Con A-induced hepatic injury; apoptosis; LECT2; TNF-a and IFN-g mRNA bent assay (ELISA), as described previously.10) Briefly, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…LECT2 is predominantly expressed in the liver and is a direct target gene of Wnt/␤-catenin signaling (2)(3)(4)(5)(6). Accumulating evidence shows that mammalian LECT2 is a multifunctional protein that is closely associated with several diseases of worldwide concern, including hepatitis (7), rheumatoid arthritis (8 -10), hepatocellular carcinoma (HCC) (11,12), obesity (13,14), and renal and hepatic amyloidosis (15)(16)(17).…”
Section: Leukocyte Cell-derived Chemotaxin 2 (Lect2)mentioning
confidence: 99%
“…LECT2 is predominantly expressed in the liver and is a direct target gene of Wnt/␤-catenin signaling (2)(3)(4)(5)(6). Accumulating evidence shows that mammalian LECT2 is a multifunctional protein that is closely associated with several diseases of worldwide concern, including hepatitis (7), rheumatoid arthritis (8 -10), hepatocellular carcinoma (HCC) (11,12), obesity (13,14), and renal and hepatic amyloidosis (15)(16)(17).…”
Section: Leukocyte Cell-derived Chemotaxin 2 (Lect2)mentioning
confidence: 99%
“…[20][21][22] A cytokine is involved in the regulation of hepatocyte activity and functions as an immunomodulator. 23 A polymorphism (Val58Ile) in the LECT2 gene (LECT2) was demonstrated to be a risk factor for the progression of rheumatoid arthritis. 24 We investigated the expression of LECT2 protein and mRNA in hepatic amyloidosis and in normal and neoplastic tissues (supplemental Table 2).…”
Section: Pathogenesis Of Hepatic Alect2 Amyloidosismentioning
confidence: 99%
“…[11][12][13][14][15][16][17] It was originally identified as a novel neutrophil-chemotactic protein by Yamagoe et al in 1996. 17 LECT2 is a 16-kDa protein that consists of 133 amino acids and three intra-molecular disulfide bonds. 18,19 The human LECT2 gene consists of four exons and three introns.…”
Section: Introductionmentioning
confidence: 99%
“…Kameoka et al 11 reported a polymorphism of the human LECT2 gene in the Japanese population associated with a severe form of rheumatoid arthritis that leads to progressive joint destruction. Using the concanavalin A-induced hepatic injury model, Segawa et al 15 reported that LECT2 expression in the mouse liver was inversely regulated by TNF-a and/or IFN-g. Saito et al…”
Section: Introductionmentioning
confidence: 99%